The Factor of Intention to Buy Snacks Labeled Halal on Muslim Students in Yogyakarta - Efendi, Riyanto (IQTISHADIA, 2019)
In the industrial era 4.0 as it is now making the food industry increasingly diverse and easy to reach all walks of life. Food consumed by the community must be good and healthy because every time it is circulated it does not necessarily make it healthy and does not have a halal label. That way, the Muslim community certainly must choose foods that are good, healthy, and halal for consumption. So the purpose of this study was to determine the effect of subjective norms, perceptions of behavioral control, and religion on the intention to buy halal labeled snacks for Muslim students. Methodology This study was a quantitative study involving 174 students taken with the Snowball Sampling technique. Methods of multiple linear regression data analysis using SPSS Version 20. The results of the study are as follows: (1). Subjective norms have a positive and significant effect on the intention to buy snacks for Muslim students, (2). The perceived behavioral control has a positive and significant effect on the intention to buy snacks for Muslim students, (3). Reliability has a positive and significant effect on the intention to buy snacks for Muslim students, (4). Subjective norms, perceptions of control, and Religiosity jointly influence the intention to buy snacks products labeled halal 36.8%.